Occupational exposure to silica dust in France: an ongoing concern - Laurène Delabre; Marie-Tülin Houot; Adrianna Burtin; Corinne Pilorget (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVES: Crystalline silica is found in many construction materials. Although it is one of the oldest known occupational exposures, new exposure contexts have emerged in recent years. In 2021, France classified work involving exposure to respirable crystalline silica (ie, silica dust) generated by a work process as carcinogenic. In order to assess exposure in the French workforce between 1947 and 2020, we developed a silica job-exposure matrix (JEM) for the Matgéné program. METHOD: The JEM was linked with occupational data from different population censuses (1982, 1990, 1999, 2007 and 2017). The proportions and numbers of workers exposed to silica dust in France at these various census time points were estimated and described by sex and industry for 2017. RESULTS: After decreasing between 1982 and 1999, the proportion of workers exposed to silica dust remained stable at 4%, representing 975 000 workers in 2017. Exposed workers were mostly men (93%), and most worked in the construction industry (64%). This was also the industry where the majority of workers were exposed to a level above the French 8-hour time weighted average occupational exposure limit (TWA-OEL). CONCLUSION: A large number of workers in France were still exposed (some highly) to silica dust in 2017 so this agent still poses an occupational health concern. The results of this study provide key information about the continued surveillance of the evolution of exposure to silica dust. In a few years, it will be possible to quantify the impact of the 2021 regulation in terms of proportions and number of workers exposed to silica dust.